Electrical Stimulation Type (Body Relax) in the Treatment of Chronic Lower Back Pain for the Players Physical Strength - Isam Talib Abbas (Journal of Global Pharma Technology, 2018)
Chronic back pain is one of the most common injuries in physical strength players. The importance of research is to relieve pain in the lower back muscles and reduce the complications that result from chronic pain reduction using a type of electrical stimulation with frequencies dedicated to muscle relaxation. The problem of research lies in the lack of use of technical means of effective and direct impact in the rehabilitation of lower back injuries of physical strength players, especially that this group of players need special care in the process of rehabilitation. The aim of the research was to use the electromyostimulate (EMS) type body relax in the treatment of chronic low back pain and to know its effect on those with the pain. The researchers used the electrical stimulation used by the researchers to have a positive effect in reducing chronic pain and rehabilitation of the lower back muscles of the physical strength players in question. The research method used the experimental method of one group and identified the research community of players with low back pain in the physical strength of the successors in Najaf, and the sample of the study (6) injured players were chosen by deliberate method, and used the form of measuring the degree of pain according to the test Shopper and physical tests The training program included the use of EMS for muscle relaxation. The researchers used the statistical program (SPSS) and used the following statistical means (median, spring deviation, and toxin).The most important conclusions reached by the researchers are:1. The electrical stimulation of the body relax is a major role in reducing the level of chronic low back pain and improve the physical flexibility of the muscles of the lower back of the players of physical strength.Keywords: Electrical stimulation, Chronic, Lower back pain and Physical strength.